Empowering Patients during Hospitalization: Perspectives on Inpatient Portal Use - McAlearney, Ann Scheck; Fareed, Naleef; Gaughan, Alice; MacEwan, Sarah R.; Volney, Jaclyn; Sieck, Cynthia J. (Applied Clinical Informatics, 2019)
Background Patients have demonstrated an eagerness to use portals to access their health information and connect with care providers. While outpatient portals have been extensively studied, there is a recognized need for research that examines inpatient portals.Objective We conducted this study to improve our understanding about the role of a portal in the context of inpatient care. Our study focused on a large sample of the general adult inpatient population and obtained perspectives from both patients and care team members about inpatient portal use.Methods We interviewed patients (n = 120) who used an inpatient portal during their hospitalization at 15 days or 6 months after discharge to learn about their portal use. We also interviewed care team members (n = 331) 4 weeks, 6 months, and 12 months after inpatient portal implementation to collect information about their ongoing perspectives about patients' use of the portal.Results The perspectives of patients and care team members generally converged on their views of the inpatient portal. Three features—(1) ordering meals, (2) looking up health information, and (3) viewing the care team—were most commonly used; the secure messaging feature was less commonly used and of some concern to care team members. The inpatient portal benefited patients in four main ways: (1) promoted independence, (2) reduced anxiety, (3) informed families, and (4) increased empowerment.Conclusion Inpatient portals are recognized as a tool that can enhance the delivery of patient-centered care. In addition to empowering patients by increasing their sense of control, inpatient portals can support family members and caregivers throughout the hospital stay. Given the consistency of perspectives about portal use across patients and care team members, our findings suggest that inpatient portals may facilitate shifts in organizational culture that increase the patient centeredness of care and improve patient experience in the hospital context.
Keywords: patient portals; hospitalization; medical informatics; engagement; empowerment